Past Tense Pronunciation Regular Verbs Ending in ED - Rojas Vite, Cristhian (Ciencia Huasteca Boletín Científico de la Escuela Superior de Huejutla, 2018)
We all know that regular verbs have the same ending in the past tense (-ed) and sometimes it is a little bit complicated to make a difference, particularly in sounds; but when someone is speaking English this person needs to speak clearly to be understood.